2009
DOI: 10.1177/0022034508328627
|View full text |Cite
|
Sign up to set email alerts
|

EDA Gene Mutations Underlie Non-syndromic Oligodontia

Abstract: Recent studies have detected mutations in the EDA gene, previously identified as causing X-linked hypohidrotic ectodermal dysplasia (XLHED), in two families with X-linked non-syndromic hypodontia. Notably, all affected males in both families exhibited isolated oligodontia, while almost all female carriers showed a milder or normal phenotype. We hypothesized that the EDA gene could be responsible for sporadic non-syndromic oligodontia in affected males. In this study, we examined 15 unrelated males with non-syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 21 publications
5
92
1
4
Order By: Relevance
“…PAX9 sequence alterations lead to agenesis mainly of molars [15,21] and MSX1 mutations have been implicated primarily in congenitally missing premolars [22,23]. Severe agenesis of both molars and premolars has been noted in patients with an AXIN2 mutation [24] whereas missing incisors are the chief manifestation of EDA-associated non-syndromic oligodontia [20,[25][26][27].…”
Section: Genes Involved In Tooth Development and Differentiationmentioning
confidence: 99%
“…PAX9 sequence alterations lead to agenesis mainly of molars [15,21] and MSX1 mutations have been implicated primarily in congenitally missing premolars [22,23]. Severe agenesis of both molars and premolars has been noted in patients with an AXIN2 mutation [24] whereas missing incisors are the chief manifestation of EDA-associated non-syndromic oligodontia [20,[25][26][27].…”
Section: Genes Involved In Tooth Development and Differentiationmentioning
confidence: 99%
“…Mutations in this gene cause X-linked hypohydrotic ectodermal dysplasia which is a rare disease. Non-sense and point mutations occurring in EDA gene cause only hypo/oligodontia which is non syndromic tooth agenesis [24].…”
Section: Eda1 Genementioning
confidence: 99%
“…EDA is a trimeric type II transmembrane protein that can release the trimer TNF core domain, which can then bind its receptor ectodysplasin-A receptor (EDAR) (Chen et al, 2001). A previous study demonstrated that the TNF homology domain is crucial for the structure and function of the EDA protein (Song et al, 2009). This domain is located at the C-terminal end of the protein and is composed of 10 predicted antiparallel β-sheets, which are necessary for the binding of EDA to EDAR (Ezer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%